To solve this system of equations, we can set the two equations equal to each other and solve for x:
(3/4)x - 7 = -3/4x - 7
Multiplying both sides by 4 to eliminate the fractions, we get:
3x - 28 = -3x - 28
Adding 3x to both sides:
6x - 28 = -28
Adding 28 to both sides:
6x = 0
Dividing both sides by 6:
x = 0
Now that we have the value of x, we can substitute it back into either of the original equations to solve for y. Let's use the first equation:
y = (3/4)(0) - 7
y = -7
Therefore, the solution to the system of equations is x = 0 and y = -7.
Solve the system of equations graphed on the coordinate axes below.
y, equals, start fraction, 3, divided by, 4, end fraction, x, minus, 7
y=
4
3
x−7
y, equals, minus, start fraction, 3, divided by, 4, end fraction, x, minus, 7
y=
−
4
3
x−7
1 answer